Studi Analisis Pengaruh Debit Air Terhadap Daya yang dihasilkan Pembangkit Listrik Tenaga Mikro Hidro (PLTMH) di Kecamatan IV Nagari Bayang Utara - Nasrul - - (Jurnal Ilmiah Poli Rekayasa, 2016)
In the district IV Nagari of North Bayang there are rivers that have a large water flow. Given its geographical position, these rivers has a large enough height difference. These rivers provide great opportunities for the development of electric energy generation in microscale powerplants.This District only have 2 villages that reserved the electricity, while others not covered due to the difficult path impassable and distances. So as to provide the electricity needs of society, the government in collaboration with the PNPM Mandiri established several microhydro powerplants (PLTMH), because of the potential for water in this place is quite large and abundant.PLTMH in this District is among PLTMH Muaro Aie 72.5 kW, PLTMH Pulai Indah 60 kW, PLTMH Bayang Janiah 15 kW, PLTMH Pancuang Taba 75 kW, PLTMH Limau-Limau 25 kW and PLTMH Ngalau Gadang 25 kW. By doing this analysis study can be known the potential of water flow on the PLTMH Muaro Aie and Pulai Indah. Due to the large potential of water flow present then the power raised also will be bigger, and new plants can be built or added to distribute the power to other areas that have not been fed by electrical energy.